Pengaruh Penerapan Model Pembelajaran Probing Prompting Terhadap Kemampuan Berpikir Kritis Pada Materi Larutan Elektrolit dan Non Elektrolit - Sarinawati (Jurnal Riset Pendidikan Kimia (JRPK), 2020)
AbstractThe purpose of this study was for knowing whether there was a difference and an effect of Probing Prompting Learning model toward student critical thinking ability. It was a quasi-experimental research, using experimental and control groups that would determine the difference of two variables. There were two sample classes—the tenth-grade students of MIA 4 (experiment) that were 28 students taught by using Probing Prompting Learning model and 28 students of MIA 5 (control) taught by using conventional learning. Collecting the data was done by using written posttest, and the obtained data were analyzed by using Independent sample t-test and Simple linear regression test. Based on the result of processing the final data, it was obtained the score of Sig. (2-tailed) 0.000 that was lower than 0.05 (0.000<0.05). It could be concluded that Ha was accepted and H0 was rejected. It meant that there was a difference between Probing Prompting Learning model and conventional learning toward student critical thinking ability. The equation of the regression was Y=56.658+0.351 X. It could be known that the score of the significance (sig.) 0.001 was lower than the probability 0.05 (0.001<0.05), so it could be concluded that Ha was accepted and H0 was rejected. It meant that there was an effect of Probing Prompting Learning model toward student critical thinking ability at the tenth grade of Senior High School of Muhammadiyah 1 Pekanbaru. KeywordsProbing Prompting Learning, Critical Thinking, Electrolyte and Non-Electrolyte Solution